Report of the National Task Force on Education (Green Paper) - Trinidad and Tobago. National Task Force on Education (Ministry of Education, Trinidad and Tobago, 1993)
This report is a comprehensive policy framework containing the essential ingredients of a plan for educational development over the following decade. It is presented in 8 sections: Section 1, the introduction includes the mission statement philosophy, contextual indicators, strategic initiatives, and critical issues; Section 2 looks at the major parameters within which educational development is likely to take place over the next decade; Section 3 presents a summary of recommendations; Section 4 outlines strategies and procedures for the management of resources within the education system; Section 5 looks at curriculum management and teacher education; Section 6 details the delivery mechanisms necessary at each level of the system; Section 7 schematically presents an action plan; and Section 8 suggests matters that constitute emerging priorities beyond the year 2000.
Keywords: National Task Force on Education; Green Paper